Battling COVID-19 leveraging nanobiotechnology: Gold and silver nanoparticle–B-escin conjugates as SARS-CoV-2 inhibitors - Zatla Ilyes; Boublenza Lamia (Open Life Sciences)
The COVID-19 pandemic, an unprecedented global health crisis, has thrust humanity into a relentless battle with a variety of treatments and vaccines against the SARS-CoV-2 virus. Recent developments in nanotechnology have garnered significant interest in the application of metallic nanoparticles (NPs); specifically, silver nanoparticles (AgNPs) and gold nanoparticles (AuNPs) have demonstrated antimicrobial and antiviral properties. This study investigates the molecular interactions between the receptor binding domains of five SARS-CoV-2 spike protein variants (Alpha, Beta, Delta, Omicron, and Gamma) and the angiotensin-converting enzyme 2 (ACE2) receptor, followed by the docking of AuNPs and AgNPs and the natural compound Beta-escin onto these complexes. As well as the inspection of both NPs against the virus main protease (Mpro) and RNA-dependent RNA polymerase (RdRp). Comprehensive computational simulations utilizing Autodock 4.2 and HDOCK server were employed to evaluate the binding affinities of these NPs toward key viral targets, SARS-CoV-2 Mpro, RdRp, and the spike glycoprotein. The results revealed that both AgNPs and AuNPs exhibited successful binding to the active pockets of SARS-CoV-2 Mpro, with slightly varying binding energies. In contrast, for RdRp, AgNPs demonstrated superior binding affinity compared to AuNPs, with differences in the residues involved in the binding pocket. AuNPs exhibited stronger binding affinities in the spike protein pocket. We also determined robust binding affinities between ACE2 and the spike variants, with the Omicron variant exhibiting the highest affinity. Subsequent docking of AuNPs and AgNPs revealed strong interactions with all ACE2–spike complexes, with AuNPs showing slightly higher affinities. The findings contribute to a deeper understanding of the interactions between NPs and viral proteins, shedding light on their mechanisms of action and their potential to offer innovative solutions for combating infectious diseases, particularly those caused by SARS-CoV-2.